An Intersectional Approach to Equity, Inequity, and Archaeology: A Pathway through Community. Issue 4 (November 2022) - Rivera Prince, Jordi A.; Blackwood, Emily M.; Brough, Jason A.; Landázuri, Heather A.; Leclerc, Elizabeth L.; Barnes, Monica; Douglass, Kristina; Gutiérrez, María A.; Herr, Sarah; Maasch, Kirk A.; Sandweiss, Daniel H.
ABSTRACT: The year 2020 was an awakening for some. For others, it reiterated the persistent social injustice in the United States. Compelled by these events, 30 diverse individuals came together from January to May 2021 for a semester-long seminar exploring inequity in archaeological practice. The seminar's discussions spotlighted the inequity and social injustices that are deeply embedded within the discipline. However, inequity in archaeology is often ignored or treated narrowly as discrete, if loosely bound, problems. A broad approach to inequity in archaeology revealed injustice to be intersectional, with compounding effects. Through the overarching themes of individual, community, theory, and practice, we (a subset of the seminar's participants) explore inequity and its role in various facets of archaeology, including North–South relations, publication, resource distribution, class differences, accessibility, inclusive theories, service to nonarchaeological communities, fieldwork, mentorship, and more. We focus on creating a roadmap for understanding the intersectionality of issues of inequity and suggesting avenues for continued education and direct engagement. We argue that community-building—by providing mutual support and building alliances—provides a pathway for realizing greater equity in our discipline.